Filtered orthogonal frequency division multiplexing for improved 5G systems - Ammar A. Sahrab; Alaa Doohee Yaseen (Bulletin of Electrical Engineering and Informatics, 2021)
Wireless communications became an integrated part of the human life. Fifth generation (5G) is the modern communication which provides enhanced mobile broadband (eMBB), ultra reliable low latency communications (URLLC), and massive machine type communication (mMTC). Thus, 5G have to provide coverage to multi-numerology devices, therefore, modulation and access schemes are suggested in the literature such as cyclic prefix orthogonal frequency division multiplexing (CP-OFDM) and filtered OFDM (f-OFDM). CP-OFDM suffers from the high out of band emission which limited the multi-numerology applications. In f-OFDM, the out of band emission can be suppressed to an accepted extent such that different numerologies can be coexisting. On the other hand, f-OFDM can be more improved by using a proper filtering approach. In this paper three different filters are suggested based windowed-sinc function; Hanning, Hamming, and Blackman. Simulation results show that the proposed filters are promising for high spectral efficiency and out of band emission rejection. Furthermore, the bit error rate, error vector magnitude, and power spectral density are further improved with respect to CP-OFDM scheme but some trade-off is present. Overall, the suggested windowed-sinc filters are outperforming the traditional CP-OFDM. As a conclusion, the suggested windnowed-sinc filters have no limitations on the modulation order or the number of subcarriers utilized in the system.